An EFL Learners’ Performances on Associating English proverbs with Equivalent Turkish Proverbs: A Cross-Cultural Study - Kimsesiz, Fatma (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2022)
As verbal folklore genres, proverbs are an essential part of cultural, social, and linguistic patterns in a given language, yet with universal tendencies present in all languages. As cultural mirrors of a given culture, proverbs may pose a resemblance in meaning and structure across cultures. There are growing appeals for translation studies that revolve around contrasting and investigating equivalent proverbs in the source language and the target language. This is the focus of the current study that aims to examine the performance of Turkish learners of English in translating selected English proverbs in terms of their interlingual equivalents in Turkish based on the theory of re-conceptualization on a comparative basis. Through the study, as an initial step 15 English proverbs were selected and examined under the scope of their re-conceptualization degrees to indicate their level of equivalency in three distinct levels as highly equivalent, roughly equivalent, and non-equivalent proverbs. As a second step, 80 learners of EFL at A2 levels participated in translating 3 groups of proverbs, and later their performance in translating these proverbs was examined and analyzed. The study is a quantitative study and the data was collected through papers uploaded by the learners on an online education program that enables remote learning called AYDEP (Ahi Qualification-Based Education Program), administered by Kırşehir Ahi Evran University. The results indicated that learners performed better in translating maximally equivalent interlingual English proverbs than roughly equivalent proverbs, and they translated and interpreted non-equivalent proverbs differently. Given these points, intertwining an intercultural affinity between the source language and the target language, interlingual equivalent proverbs prove to have facilitating roles in associating English proverbs with Turkish equivalents.